2011
DOI: 10.3856/vol39-issue2-fulltext-14
|View full text |Cite
|
Sign up to set email alerts
|

Asociacion entre la tasa de autofecundacion y la frecuencia de larvas malformadas en poblaciones cultivadas del ostion del norte Argopecten purpuratus (Lamarck, 1819)

Abstract: RESUMEN. El incremento de la frecuencia de malformaciones y la reducción de la viabilidad y fecundidad suelen ser las primeras manifestaciones de la depresión por consanguinidad en animales. El ostión del norte, Argopecten purpuratus (Lamarck, 1819), es una especie hermafrodita funcional con autofecundación parcial y durante la reproducción artificial puede presentar altos grados de autofecundación. En este trabajo se analizó la asociación de la tasa de autofecundación con la frecuencia de larvas malformadas y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
1
4
0
1
Order By: Relevance
“…The data registered during the controlled spawning process indicate that 0%–25% of zygotes per family began spontaneous embryonic development after the gametes release, with an average of 12%, presumably due to self‐fertilization. Such levels of selfing are similar to those reported for other species of hermaphroditic mollusks, like A. purpuratus (Toro, Montoya, Martínez, Gutiérrez, & Vergara, ; Winkler & Estévez, ) and Radix balthica (7%–20%; Bürkli et al, ) under similar experimental conditions, although in A. purpuratus the selfing rates can be very variable among different females (Concha, Figueroa, & Winkler, ; Toro et al, ; Winkler & Estévez, ). In addition, the occurrence of self‐fertilization has been verified by molecular analysis of massive spawns in farmed A. irradians (Li & Li, ) and N. subnodosus (Petersen, Ibarra, Ramirez, & May, ).…”
Section: Discussionsupporting
confidence: 87%
“…The data registered during the controlled spawning process indicate that 0%–25% of zygotes per family began spontaneous embryonic development after the gametes release, with an average of 12%, presumably due to self‐fertilization. Such levels of selfing are similar to those reported for other species of hermaphroditic mollusks, like A. purpuratus (Toro, Montoya, Martínez, Gutiérrez, & Vergara, ; Winkler & Estévez, ) and Radix balthica (7%–20%; Bürkli et al, ) under similar experimental conditions, although in A. purpuratus the selfing rates can be very variable among different females (Concha, Figueroa, & Winkler, ; Toro et al, ; Winkler & Estévez, ). In addition, the occurrence of self‐fertilization has been verified by molecular analysis of massive spawns in farmed A. irradians (Li & Li, ) and N. subnodosus (Petersen, Ibarra, Ramirez, & May, ).…”
Section: Discussionsupporting
confidence: 87%
“…It is known that other factors like self-fertilization, high egg : sperm ratio, temperature, and pollutants may cause an increase in larval deformities (Conroy et al, 1996;Spangenberg and Cherr, 1996;His et al, 1997;Krassoi et al, 1997, Concha et al, 2011Kobayashi and Kijima, 2010). It has also been reported that factors in the rearing environment such as small rearing volumes, stagnant systems, addition of antibiotics, or pulse feeding may cause larvae deformities in control groups (Kurihara et al, 2007(Kurihara et al, , 2008Talmage and Gobler, 2009Waldbusser et al, 2010;Gaylord et al, 2011;Gazeau et al, 2011).…”
Section: Shell Deformitiesmentioning
confidence: 99%
“…It is known that other factors like self-fertilization, high egg : sperm ratio, temperature, and pollutants may cause an increase in larval deformities (Conroy et al, 1996;Spangenberg and Cherr, 1996;His et al, 1997;Krassoi et al, 1997, Concha et al, 2011Kobayashi and Kijima, 2010). It has also been reported that factors in the rearing environment such as small rearing volumes, stagnant systems, addition of antibiotics, or pulse feeding may cause larvae deformities in control groups (Kurihara et al, 2007(Kurihara et al, , 2008Talmage and Gobler, 2009Waldbusser et al, 2010;Gaylord et al, 2011;Gazeau et al, 2011).…”
Section: Shell Deformitiesmentioning
confidence: 99%